2007
DOI: 10.1016/j.jalgebra.2006.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The derived series of a finite p-group

Abstract: Let G be a finite p-group, and let G (d) denote the dth term of the derived series of G. We show, for p 5, that G (d) = 1 implies log p |G| 2 d + 3d − 6, and hence we improve a recent result by Mann.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The interest on p-groups without proper subgroups with the same derived length has been related with the problem of bounding the order of a finite p-group in terms of its derived length (a long history starting from Burnside's papers, see [5] for more details). Mann [4] showed that if G is a finite p-group, then G (d) = 1 implies log p |G| > 2 d + 2d − 2.…”
Section: Introductionmentioning
confidence: 99%
“…The interest on p-groups without proper subgroups with the same derived length has been related with the problem of bounding the order of a finite p-group in terms of its derived length (a long history starting from Burnside's papers, see [5] for more details). Mann [4] showed that if G is a finite p-group, then G (d) = 1 implies log p |G| > 2 d + 2d − 2.…”
Section: Introductionmentioning
confidence: 99%